PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN WORDWALL TERHADAP BUDAYA LITERASI DIGITAL PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS 3 SDN BOJONGKAWUNG - Agnia aulia, Tiara; Dyah Lyesmaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of using Wordwall learning media on the digital literacy culture of third-grade students at SDN Bojongkawung in Indonesian language learning. The research employed a quantitative approach with a descriptive method. The participants consisted of 15 third-grade students who were selected using a saturated sampling technique, meaning that all members of the population were included as research samples. Data collection techniques included questionnaires, observation, and documentation. The research instruments consisted of a digital literacy questionnaire sheet and a learning activity observation sheet designed based on predetermined indicators of digital literacy. The collected data were analyzed using descriptive quantitative analysis with the assistance of IBM SPSS Statistics, involving the calculation of minimum, maximum, and mean values to describe students’ digital literacy levels. The results of the study indicate that the use of Wordwall learning media has a positive influence on students’ digital literacy culture. This is evidenced by the questionnaire results showing a minimum score of 21, a maximum score of 31, and a mean score of 27.4, which is categorized as moderately high. Observation results also revealed that students became more active, enthusiastic, and engaged during the learning process, particularly in participating in interactive and game-based activities using Wordwall. Furthermore, documentation showed that students were able to interact effectively with digital learning media both individually and in groups, indicating improved familiarity with digital tools in learning activities. Overall, Wordwall learning media creates an interactive and enjoyable learning environment that encourages student participation and supports the development of digital literacy skills from an early age. In conclusion, Wordwall is effective in enhancing the digital literacy culture of elementary school students in Indonesian language learning.